Are fire services 'extremely gendered' organizations? Examining the Country Fire Authority (CFA) in Australia. Issue 9 (29th July 2019) - Tyler, Meagan; Carson, Lisa; Reynolds, Benjamin
Abstract : Emergency management organizations often have military‐based histories and continue to maintain militaristic styles of operation. Similar to the military, these organizations tend to be male dominated and culturally masculinized. The militarization and masculinization of rural fire services in Australia are generally unrecognized but highly important elements defining these organizations, and the example of the Country Fire Authority (CFA) is considered here. Using a cultural artefacts approach, historical and contemporary elements of the CFA's structure and practice are analysed using the concept of an 'extremely gendered' organization, with a focus on how the CFA is structurally and culturally gendered. We argue there is value in expanding the notion of 'extremely gendered' institutions beyond the military, to include other militarized organizations. Doing so not only helps to better understand and address resistance to change and gender equality measures, it also draws attention to the important role that such organizations play in the greater patriarchal order.